POLA PERGERAKAN DAN WILAYAH JELAJAH GAJAH SUMATRA (Elephas maximus sumatranus) DENGAN MENGGUNAKAN GPS RADIO COLLAR DI SEBELAH UTARA TAMAN NASIONAL TESSO NILO, RIAU - Erwanda Trio Bintan Sabri; Haris Gunawan; Khairijon ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The Sumatran Elephant is one of the largest land mammal species that exist on the island of Sumatra which is currently critically endangered. The main threat for Sumatran elephant conservation is the fragmentations of its habitat which have been causing a conflict between elephants and humans. Tesso Nilo National Park is an area used as the original habitat of the Sumatran elephants which has now undergone encroachment. Conflicts between humans and elephants have become a much-talked-about issue and a factor which cause the depletion of population of the Sumatran elephant. This research aimed to determine the pattern of movement and the use of space by Sumatran elephants in the habitat that has experienced disturbance by human using GPS Collar and GIS technologies. The data of this research was acquired by attaching a GPS Collar on the leader of the elephant clan and processed using excel and arcGis program. This research was conducted from January 2013 to January 2014 in the northern part of Tesso Nilo National Park (TNTN). The results showed that the daily movement pattern of the elephant was random with an area of 56.631 ha and through several different land types. The elephant preferred a land type with more dense canopy and less disturbance.